Understanding the Meaning and Importance of Philosophy of Education for Performing Arts Education Students: A Case Study - Roy Martin Simamora; Sarjiwo; Syafiq Faliq (Indonesia Approach Education, 2024)
This case study explores the meaning and importance of the philosophy of education for students studying in the performing arts education department. By examining the beliefs, values, and educational philosophies of performing arts students, this study aims to uncover the profound impact of philosophy on their educational experiences and future artistic endeavors. This study utilized a case study approach. Questionnaires were administered to performing arts education students. The questionnaire consisted of eight questions that were carefully structured to uncover the students' views, beliefs, and experiences relating to the philosophy of education. Data collection was conducted online through Google Forms. Google Forms were then distributed to 35 participants in early May 2023. After the deadline for form completion at the end of May 2023, responses from the participants were automatically collected by Google Forms. The responses were then aggregated and an in-depth analysis was conducted to look at themes, patterns, and relationships prevalent in the responses. The results of this study highlight the role of diverse educational philosophies in shaping learning experiences, influencing academic achievement, and impacting educational policy and practice. This study enriches the dialogue on performing arts education, providing valuable insights for educators and policymakers. By elevating the discussion from visible aspects to the underlying philosophical structure, it offers an innovative approach for a more holistic educational experience for performing arts students.